Reynolds and prandtl numbers effects on mhd mixed convection in a lid-driven cavity along with joule heating and a centered heat conducting circular block - Rahman, M.M.; Billah, M.M.; Mamun, M.A.H.; Saidur, Rahman; Hasanuzzaman, M. (International Journal of Mechanical and Materials Engineering, 2010)
The fluid flows and heat transfer induced by the combined effects of mechanically driven lid and buoyancy force within a rectangular cavity is investigated in this paper numerically. The horizontal walls of the enclosure are insulted while the right vertical wall is maintained at a uniform temperature higher than the left vertical wall. In addition, it contains a heat conducting horizontal circular block in its centre. The governing equations for the problem are first transformed into a non-dimensional form and the resulting nonlinear system of partial differential equations are solved by using the finite element formulation based on the Galerkin method of weighted residuals. The analysis is conducted by observing the variations of streamlines and isotherms for different Reynolds number and Prandtl number ranging from 50 to 200 and from 0.071 to 3.0 respectively. The results indicated that both the streamlines and isotherms strongly depend on the Reynolds number and Prandtl number. Moreover, the results of this investigation are also illustrated by the variations of average Nusselt number on the heated surface and average fluid temperature in the enclosure.